2005
DOI: 10.1038/nn1386
|View full text |Cite|
|
Sign up to set email alerts
|

A representation of the hazard rate of elapsed time in macaque area LIP

Abstract: The capacity to anticipate the timing of environmental cues allows us to allocate sensory resources at the right time and prepare actions. Such anticipation requires knowledge of elapsed time and of the probability that an event will occur. Here we show that neurons in the parietal cortex represent the probability, as a function of time, that a salient event is likely to occur. Rhesus monkeys were trained to make eye movements to peripheral targets after a light dimmed. Within a block of trials, the 'go' times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

58
638
4
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 542 publications
(703 citation statements)
references
References 46 publications
58
638
4
3
Order By: Relevance
“…Notice the strong rise of activity in visuomotor F5a neurons in anticipation of the GO cue (Fig. 9B, left), which is reminiscent of the climbing activity in LIP (lateral intraparietal area) neurons during saccade tasks (Janssen and Shadlen, 2005;Premereur et al, 2011).…”
Section: Population Analysis Of Grasping Activity In F5amentioning
confidence: 87%
“…Notice the strong rise of activity in visuomotor F5a neurons in anticipation of the GO cue (Fig. 9B, left), which is reminiscent of the climbing activity in LIP (lateral intraparietal area) neurons during saccade tasks (Janssen and Shadlen, 2005;Premereur et al, 2011).…”
Section: Population Analysis Of Grasping Activity In F5amentioning
confidence: 87%
“…The hazard functions obtained from the f ON densities will be referred to as the "f ON hazard rates." It has been suggested that hazard rates are estimated and used to guide behavior (Ghose and Maunsell, 2002;Janssen and Shadlen, 2005;Oswal et al, 2007). The latency of anticipatory pursuit movements could be considered as the outcome of this process.…”
Section: Hazard Ratementioning
confidence: 99%
“…In a visual detection task, it has been shown that the hazard rate could be used to guide the allocation of attention in the time domain (Ghose and Maunsell, 2002). Moreover, it has been shown that a subjective estimate of the hazard rate could describe the behavioral consequence of the anticipation of a "go" signal in a saccade task and could be represented in the LIP (lateral intraparietal area) of the macaque monkey (Janssen and Shadlen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Neurons in lateral intraparietal area (LIP) seem to represent the passage of time relative to a remembered standard duration (Leon and Shadlen, 2003). Janssen and Shadlen (2005) recorded the activity of LIP neurons while monkeys made saccades to peripheral targets after a variable delay period. The timing of the "Go" signal (dimming of the fixation point) was a random value whose probability distribution was fixed throughout a block of trials.…”
Section: Neural Bases and Modelsmentioning
confidence: 99%
“…By now, many studies indicate that we can use temporal information flexibly and across multiple sensory modalities to orient at-tention selectively to specific intervals (Griffin et al, 2001;Lange et al, 2003;Correa et al, 2004). Positron emission tomography and fMRI studies have shown that control of temporal orienting in speeded-response tasks involves brain areas that participate in spatial orienting of attention as well as areas that participate in motor control (Coull and Nobre, 1998;Coull et al, 2000), including posterior parietal cortex, in which cellular correlates of temporal predictability have been identified (Janssen and Shadlen, 2005). Despite the sizeable overlap of brain areas participating in temporal and spatial orienting, the neural mechanisms involved in anticipating and modulating stimulus processing when each type of orienting occurs in isolation can differ substantially (Nobre, 2004).…”
Section: Neural Bases and Modelsmentioning
confidence: 99%